The reconstruction of Muslim women’s property rights in the 21st Century - Kamaruddin, Zaleha (Equinox Publishing Ltd, 2020)
In the quest towards empowering women, different societies have introduced phenomenal reforms over the centuries but there still exist significant limitations in certain communities across the world. The Muslim world has been a focal point for most human rights activists. The general perception persists regarding equal access and opportunities for women in their pursuit of property rights. The frequently headlined point of ratio two to one in the Muslim inheritance share of men and women has been overstretched without any meaningful consideration to how women access other property rights through legitimate means provided under the Islamic law as well as other seemingly Sharī‘ah-compliant provisions in conventional human rights instruments. The modern dynamics underlying women’s property rights and the continued struggle towards securing such rights within complex societies that are tainted with pseudo-religious practices and mummified by deep-rooted cultural norms lead to two simultaneously deficient views with special reference to Muslim societies. While the first view believes women’s property rights are curtailed and excessively limited in Islam, the second position emphasizes the postmodernist approach, which tends to gravitate towards emancipating the modern day Muslim woman. Against the above backdrop, this chapter seeks to address four pertinent questions: 1. What are other property rights Muslim women can acquire apart from inheritance, which is often perceived in some quarters as being discriminatory? 2. What are the obstacles and limits constraining the full implementation of property rights for Muslim women? 3. Can the international human rights instruments help in providing equal access to, and protection of, property rights of both men and women, and to what extent is such a legal framework accepted in Muslim states? 4. How can a fresh and balanced appreciation of Islamic principles as lobbying tools for positive interpretation be constructed in the modern world? The legal status of women under the Sharī‘ah has been a subject many Muslim jurists of the past have laboured on in their respective juristic treatises. This same concept has touched off a maelstrom of controversy across the Muslim world and beyond, particularly when it comes to the strict interpretation of the inheritance rights in Islam. While one might not need to delve into the arena of controversy among some contemporary Muslim jurists, an endeavour to look inwards within the general Sharī‘ah framework reveals a plethora of neglected Islamic legal rules that may be closely studied to evolve a new integrated and holistic transformative property regime. This will re-emphasize the relevance of Islamic legal principles in the 21st century, which is expected to lead to some sort of convergence of laws in an increasingly globalized world. Therefore, it is high time people took a step further from the culturally denied gender land rights and the perceived gender discrimination in inheritance rights in Islam. This chapter focuses on some of these potential concepts within the Islamic framework that would promote unhindered access to property rights by way of recompense bearing in mind the increasing responsibilities shouldered by women in Muslim societies across the world.